Effects of a head-cooling cap on 5-km running performance in the heat - Spannagl, B. J.; Willems, M. E.; West, A. T. (International Journal of Exercise Science, 2023)
Cooling the head region during exercise can enhance running performance, but this observation is limited to intermittent cooling. This study investigated the effects of continuous head cooling on 5-km running time-trial (TT) performance in hot conditions. Six male and four female triathletes completed two experimental sessions consisting of two 10-minute runs at 50% and 70% O2max followed by a 5-km TT in the heat (32.0±0.3 °C, 50.1±1.2% RH). In a randomized crossover design, either an ice-filled cooling cap or no cooling cap was provided prior to the 10-minute run at 70%O2max. Performance time, rectal, forehead and mean skin temperature, RPE, thermal comfort, fluid loss, blood lactate and heart rate were recorded. Performance time was faster with a cooling cap (1175±80 s) compared to no cooling cap (1189±76 s, P = 0.034; d = 0.18). The cooling cap reduced forehead temperature (P <0.001) and improved thermal comfort (P = 0.004) but had no effect on any other variable (P > 0.05). Continuously cooling the head with an ice-filled cap enhanced 5-km TT performance in the heat. Participants reported an improved thermal comfort with no change in core temperature. Continuously cooling the head may be a practical strategy to enhance running performance in hot conditions.